Perfluorane and Curosurf in the Treatment of Respiratory Distress Syndrome - N. V. Shapovalova; A. A. Lavrentyev; S. V. Yermolenko; Yu. V. Struk; V. PeshkovV. (Общая реаниматология, 2006)
The article deals with the clinical investigation of the impact of perftorane and natural surfactant on the course of Adult Respiratory Distress Syndrome. The special attention was paid to the methods of endobronchial administration of these medicines, their partial efficiency and joint synergism.